PROTOTYPE ALAT DETEKSI KEBOCORAN GAS LPG MENGGUNAKAN NODEMCU ESP8266 - Indra Maulana Yusup Kusumah; Dede Suarna Ramadhani; Efrizal Fikri Yusmansyah (LPPM STMIK BANDUNG, 2022)
Limited natural resources make humans use gas fuel. However, this gaseous fuel has a negative effect, namelyfrequent fires caused by gas explosions. In general, fires often occur in people's homes due to LPG gas explosions that cannot be anticipatedproperly.Therefore, to anticipate this, we need a tool that can detect gas leaks, so that explosions caused by gas leaks can be anticipated immediately so that the fire does not spread. The gas leak detector that will be made can detect gas leaks and provide information in the event ofa gas leak.The gas leak detector uses the MQ 2 sensor and the ESP8266 Wifi Module, LCD and buzzer, fan and fire sensor as notifications, capable of detecting gas leaks and providing information to the owner so thatfires can be anticipated as early as possible. The information generated from this tool is in the form of alarm sounds and messages sent via telegram that are sent